Jaminan Sosial di Indonesia: Relevansi Pendekatan Informal - - Mudiyono (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
Indonesia is deprived in social security system, despite the fact that the recently amended constitution retains a mandate to grant all citizen with social security. While the formal setup such as social security insurance has not been sufficiently developed, the informal practice of delivering social security system has not been seriously revived and nurtured. As the mode of governance has been incrasingly decentralised, a locally-supported social security system became a strategic challenge to meet.